Test of Methods Eliminating Regular Signal Level Variations due to Spatial Alphasat Satellite Motion - Pek, Viktor; Fišer, Ondřej; Rejfek, Luboš (My University, 2018)
Many countries receive the Alphasat satellite signal in both Ka and Q bands in order to analyze the random atmospheric attenuation. The received signal from the Alphasat satellite is influenced not only by the atmosphere but also by the quasi regular satellite motion causing the “cosinusoidal” signal level fluctuations of about 24 hour period. In this contribution we describe mathematical methods eliminating this fluctuation and perform tests of the suitability of particular methods. To test these methods we developed and used the signal level software simulator as we must know the “true” attenuation values while the simulated values are the “true” ones from our testing viewpoint. The tests showed that we should recommend the MY method developed at the Institute of Atmospheric Physics Prague but the differences among tested methods are low and all described methods are acceptable.
Test metod odstraňujících běžné fluktuační odchylky způsobené prostorovým pohybem družice Alphasat
Keywords: Satellite communication; atmospheric attenuation; satellite space motion elimination; Družicová komunikace; atmosférický útlum; eliminace prostorového pohybu družice